IMPROVING EXAMPLE-PROBLEM-BASED-LEARNING (EPBL) WITH GROW COACHING MODEL AND DESIGN SPRINT TO OPTIMIZE PRE-INCUBATION CURRICULUM: CASE STUDY OF USER INTERFACE DESIGN - Eko Heri Susanto; Ahmad Faisal Rizal; I Putu Indra Wijaya Suwina (Department of Computer Engineering, Universitas Wiralodra, 2023)
Learning to develop user interfaces is one of the subject matter in startup business pre-incubation activities in PT. Tunas Inkubator Creative Startup. The Example-Problem Based Learning (EPBL) learning method is proven to be able to improve students' cognitive abilities (hard skills). However, hard skill competence alone is not enough to measure one's ability. This research aims to improve the hard skill competencies, as well as the soft skills of the tenants. The contribution to this research is that researchers apply the GROW coaching model method to measure tenant motivation and insert design sprints into the Example-Problem-Based Learning method. Where the function of the design sprint is to improve the attitude of cooperation between teams. The improvisation of learning methods in this study aims to measure students' speed in mastering user interface design subjects. From the trial results it is known that tenants can complete the user interface design within 2 weeks.